“Memories of My Body” Movie Ban as An Effect of Dominant Anti-LGBT Discourse in Depok City - Panji Satrio Binangun; Susanto Susanto; Dwi Susanto (International Journal of Science and Applied Science: Conference Series, 2022)
"Memories of My Body" screening ban in 2019 by Depok local government is deemed problematic since it has already passed Film Censor Board (LSF). This paper aimed to better understand the decision made by the Depok local government in banning the movie through critical discourse analysis. This paper is a discourse analysis understand the discourse surrounding the movie ban in Depok.. This paper's primary data is literature studies from numerous electronic news sources. Norman Fairclough’s critical discourse analysis is used as a theory and methodology. The result from this research shows that there are two main discourses: protecting younger generation and incompatibility toward Islamic values. After further analysis, it is found that these discourses also exist in another events. This fact shows that the movie ban is an effect from a dominant discourse against LGBTQ community.